Pengaruh Good Governance, Kompetensi Aparat Desa, dan Pengawasan terhadap Efektivitas Pengelolaan Dana Desa : (Studi Empiris Desa se Kecamatan Wanasari Kabupaten Brebes) - Riri Rengganih; Anisa Sains Kharisma; Hilda Kumala Wulandari; Dumadi, Dumadi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of good governance, village official competence, and oversight mechanisms on the effectiveness of Village Fund management in Wanasari District, Brebes Regency. A quantitative approach was used, involving a questionnaire survey of 90 respondents from 20 villages. Data were analyzed using multiple linear regression. The results show that all three independent variables have both partial and simultaneous positive and significant effects on Village Fund management effectiveness. These findings suggest that improving governance practices, enhancing human resource capacity, and strengthening transparent and accountable oversight systems are crucial to optimizing the management and impact of Village Funds in rural development.